PENGEMBANGAN KEPEMIMPINAN KOLEKTIF DI PONDOK PESANTREN (STUDI KASUS DI PONDOK PESANTREN HIDAYATUL MUBTADI-IEN NGUNUT TULUNGAGUNG) - Muhammad Fathurro’uf, Muhammad Fathurro’uf; Muhammad Ali Fathan Zahrurridlo (AL-MAFAZI: JURNAL MANAJEMEN PENDIDIKAN ISLAM, 2023)
This article aims to describe and analyze the efforts of the kyai to care for the successor of Almaghfurlah KH. Muhammad Ali Shodiq Umman builds collective leadership, what obstacles are encountered in efforts to build collective leadership and the effectiveness of implementing collective leadership at the Hidayatul Mubtadi-ien Islamic Boarding School (PPHM) Ngunut Tulungagung. Collective Leadership means leadership that is organized or handled jointly according to the division of tasks for each individual. Authority or authority is not absolute in the hands of one person (individual), but is transferred to the authority or authority of several people (collective). This article uses descriptive qualitative research methods. The research results show that the efforts that have been made by all managers (caregivers, administrators and asātidh) in building collective leadership at the Hidayatul Mubtadi-ien Islamic Boarding School (PPHM) Ngunut Tulungagung are (1) forming a caretaker council, (2) consolidating the Sunan Foundation Giri, (3) structuring the structure, management and organizational mechanisms of existing institutions (4) institutionalizing deliberations/meetings/trials as decision-making forums, (5) conflict resolution, (6) cadre formation, and (7) development of funding sources . The obstacles encountered in efforts to build collective leadership at the Hidayatul Mubtadi-ien Ngunut Tulungagung Islamic Boarding School are (1) limited funds and infrastructure, (2) technical: limited ability to organize, coordinate and control the institutions at PPHM Ngunut, (3) limited knowledge and insight of managers, (4) there is still a culture of individual leadership. Effectiveness The implementation of collective leadership at the Hidayatul Mubtadi-ien Ngunut Tulungagung Islamic Boarding School was quite effective, where the efforts made had an impact on the condition of the Islamic boarding school being stable, continuing to exist and developing more advanced.